Identifying new targets for improving terpenoid biosynthesis in Yarrowia lipolytica through random genomic cytosine base editing - Zhenxia Li; Bo Liu; Rongtao Lv; Zhe Sun; QingYan Li; XueLi Zhang (Microbial Cell Factories)
Abstract Background Genome-scale mutagenesis integrated with high-throughput phenotypic screening and causal mutation mapping serves as a robust paradigm for systemic genetic dissection. Despite the application of non-homologous end joining (NHEJ)-mediated genome editing in Yarrowia lipolytica, the development of alternative genome-wide mutagenesis strategies remains unexplored in this industrially relevant oleaginous yeast. Results We developed the Helicase-Assisted (Helicase-CDA) system, a genome-wide mutagenesis platform integrating the helicase domain of Yarrowia MCM5 (Encoded by YALI1_A01766g) with cytidine deaminase (CDA). This system enables continuous C-to-T specific mutations at random genomic loci. Applied to an industrial β-carotene-producing Y. lipolytica strain, Helicase-CDA system generated a mutagenized library through 7-day subculturing. Through high-throughput screening, we successfully isolated the mutant strain CDA-14, which demonstrated a 25% enhancement in β-carotene production (448.1 mg/L) compared to the wild-type strain. Notably, its productivity of β-carotene reached 6.15 g/L in fed-batch fermentation. Whole-genome sequencing revealed a G1637A substitution in YALI1_B16239g, which encodes a membrane protein showing homology to sterol biosynthesis regulator MGA2. This mutation led to reduced ERG1 expression level and redirected central carbon flux toward carotenoid synthesis by perturbing isoprenoid precursor partitioning. Conclusion Helicase-CDA system circumvents the dependency on NHEJ-mediated whole-genome mutation approach, offering a robust tool for continuous genome evolution in pre-engineered industrial strains. This study not only enhances genome editing in Y. lipolytica but also identifies a practical target for optimizing terpenoid biosynthesis, demonstrating significant potential for applications in metabolic engineering and synthetic biology.